2020
DOI: 10.1021/acs.analchem.0c04225
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Microscale Processing: Combined Raman and Absorbance Spectroscopy for Microfluidic On-Line Monitoring

Abstract: Microfluidics have many potential applications including characterization of chemical processes on a reduced scale, spanning the study of reaction kinetics using on-chip liquid–liquid extractions, sample pretreatment to simplify off-chip analysis, and for portable spectroscopic analyses. The use of in situ characterization of process streams from laboratory-scale and microscale experiments on the same chemical system can provide comprehensive understanding and in-depth analysis of any similarities or differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…However, previous study has shown that a PLS model can accurately quantify the [Nd 3þ ] even when the [HNO 3 ] varies so long as the variation is represented in the training set. 36,37 This observation can also be applied to other metal ions. Sample spectra were referenced to a deionized water spectrum using the UV-Vis instrumental software before exporting to Matlab for study.…”
Section: Chemometric Modelingmentioning
confidence: 80%
See 1 more Smart Citation
“…However, previous study has shown that a PLS model can accurately quantify the [Nd 3þ ] even when the [HNO 3 ] varies so long as the variation is represented in the training set. 36,37 This observation can also be applied to other metal ions. Sample spectra were referenced to a deionized water spectrum using the UV-Vis instrumental software before exporting to Matlab for study.…”
Section: Chemometric Modelingmentioning
confidence: 80%
“…Preprocessing of UV-Vis spectra was done to minimize the instrumental noise and allow the model to focus on data that contained the chemical information. 11,37 Raw and post-processed training set spectra are presented in Fig. S1 (Supplemental Material).…”
Section: Chemometric Modelingmentioning
confidence: 99%
“…Additional solutions containing uranyl nitrate (98.0–102%, Spectrum Chemical Manufacturing Corporation) and U(IV) with sodium nitrate (>99%, Sigma Aldrich) and nitric acid (70%, Sigma Aldrich) were made and measured on a fused silica microfluidic chip using Raman spectroscopy. The Raman setup has been described previously as have solution preparation approaches in Lines et al 3 and Nelson et al 21,30,31…”
Section: Methodsmentioning
confidence: 99%
“…3 In addition to U(VI) (uranyl), many Purex relevant compounds are Raman active, including phosphate, nitrate, and water. 3,[18][19][20][21][22] Raman spectroscopy can also provide insight into matrix conditions relevant to spent nuclear fuel reprocessing, such as pH; for instance, the Raman water vibrational band changes in response to acid concentration. 23,24 Raman spectroscopy can be used to detect UV-Vis inactive molecules and polyatomic ions in aqueous and organic phase solutions, but it does not directly detect free, monoatomic ions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to effectively reprocess the hazardous materials in these tanks, methods of accurate characterization are necessary, allowing for a more permanent disposal . Offline lab analyses take hours to days to complete, have limited accuracy in dynamic solution environments, and require extraction and handling of hazardous samples. Fortunately, there now exists remote, immediate, online, and nondestructive analyses using optical spectroscopy. ,, Raman spectroscopy has been employed for accurate quantification of various analytes in complex systems for waste reprocessing and other areas of the nuclear cycle. , Raman probes are particularly desirable due to their ability to function in harsh environments without the need for frequent calibration. Robust detection methods for uranium, plutonium, neptunium, aqueous nitrate, gaseous iodine, and other relevant species have also been established. ,, Raman and UV–vis microprobes have been used to extend applications to the microscale, further reducing researcher exposure to hazardous materials. , Phosphoric acid and its three deprotonated species are Raman active, allowing for the application of Raman spectroscopy to phosphate systems. In our application, a Raman probe is inserted within the fuel reprocessing and related waste streams in direct contact with the solution, allowing in situ measurement.…”
mentioning
confidence: 99%